Clinical and epidemiological study of orofacial clefts - Josiane Souza; Salmo Raskin (Elsevier, 2013)
Objective: Cleft lip with or without cleft palate (CL±P) or cleft palate (CP) are groups of malformations named orofacial clefts (OC), which are the second leading cause of birth defects. This study aimed to analyze clinical and epidemiological features of Brazilian patients with OC, studying cases treated in the reference center of the state of Paraná (PR). Methods: 2,356 charts were reviewed and 1,838 were evaluated by the same clinical geneticist. Data were collected in the reference center, and compared with those of the Health Department of the state of Paraná. Clinical characteristics, presence of other anomalies, and birth prevalence were evaluated. Results: 389 (21.2%) patients had CP, 437 (23.8%) had cleft lip (CL), and 1,012 (55%) had cleft lip and palate (CLP). Syndromic OC were identified in 15.3% of patients, 10.4% of patients with CL±P, and 33.9% of patients with CP. Common additional anomalies were: central nervous system, limbs, cardiovascular, and musculoskeletal defects. The number of syndromic cases was lower when clinical evaluation was performed by other medical specialists when compared to that of the clinical geneticist. Birth prevalence was 1/1,010 live births. Lack of notification with the national birth registry was observed in 49.9% of CL±P. The present data suggests a decrease of 18.52% in the prevalence of non-syndromic OC after folic acid fortification in Brazil. Conclusion: Better understanding of clinical and epidemiological aspects of OC is crucial to improve the understanding of pathogenesis, promote preventive strategies, and guide clinical care, including the presence of clinical geneticists in the multidisciplinary team for OC treatment. Resumo: Objetivo: Fissura labial com ou sem fissura palatina (FL ± P) ou fissura palatina (FP) são grupos de malformações chamados fissuras orofaciais (FO) e são a segunda causa de defeitos congênitos. O objetivo do estudo foi analisar características clínicas e epi- demiológicas de pacientes brasileiros com FO, estudando casos tratados no centro de referência do estado do Paraná (PR). Métodos: Foram analisados 2.356 gráficos. Destes, 1.838 foram avaliados pelo mesmo geneticista clínico. Os dados foram coletados no centro de referência e analisados na Secretaria de Estado da Saúde do Paraná. Foram avaliadas as características clínicas, a presença de outras anomalias e a prevalência de nascimentos. Resultados: No total, 389 (21,2%) pacientes apresentaram fissura palatina (FP), 437 (23,8%) apresentaram fissura labial (FL) e 1.012 (55%) apresentaram fissura labiopala- tina (FLP). As FO sindrômicas foram identificadas em 15,3% dos pacientes, 10,4% dos pacientes com FL ± P, e 33,9% dos pacientes com FP. Anomalias comuns adicionais foram: sistema nervoso central, membros, sistema cardiovascular e sistema musculoesqueléti- co. O número de casos sindrômicos foi menor nos centros em que a avaliação clínica foi realizada por outros especialistas, em comparação aos locais em que ela foi realizada por um geneticista clínico. A prevalência de nascimentos foi de 1/1.010 nascidos vivos. A ausência de notificação junto ao cartório de registro civil foi observada em 49,9% dos casos de FL ± P. No Brasil, nossos dados sugerem uma redução de 18,52% na prevalência de FO não sindrômicas após a fortificação com ácido fólico. Conclusão: Um melhor entendimento dos aspectos clínicos e epidemiológicos das FO é fundamental para melhorar a compreensão de sua patogênese, promover estratégias de prevenção e promover orientações com relação a cuidados clínicos, com a presença de geneticistas clínicos na equipe multidisciplinar para tratamento de FO, por exemplo. Keywords: Orofacial cleft, Cleft lip and palate, Epidemiology, Clinical geneticist, Brazil, Palavras-chave: Fissura orofacial, Fissura labiopalatina, Epidemiologia, Geneticista clínico, Brasil